Irreducible Spacer Subluxation after Total Ankle Replacement Arthroplasty in a Patient with Rheumatoid Arthritis: A Case Report - Seo, Dong-Kyo; Kim, Sang Young (Journal of Korean Foot and Ankle Society, 2021)
End-stage ankle arthritis is a debilitating condition that causes functional limitations and consequently a poor quality of life. Total ankle replacement arthroplasty is a good alternative to arthrodesis for preserving the ankle’s range of motion. However, many complications can occur in patients with rheumatoid arthritis and with poor soft tissue and bone conditions. A 61-year-old female experienced spacer subluxation after surgery, which was not reduced by medial soft tissue release and spacer change. Buttress plating was found to be a good treatment option to prevent spacer subluxation and can be considered in patients with rheumatoid arthritis with bone erosion and soft tissue damage. KCI Citation Count: 0